2017
DOI: 10.1007/978-3-319-58703-5_29
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Usability Factors of Mid-Air Hand Gestures for 3D Virtual Model Manipulation

Abstract: Abstract. Although manipulating 3D virtual models with mid-air hand gestures had the benefits of natural interactions and free from the sanitation problems of touch surfaces, many factors could influence the usability of such an interaction paradigm. In this research, the authors conducted experiments to study the visionbased mid-air hand gestures for scaling, translating, and rotating a 3D virtual car displayed on a large screen. An Intel RealSense 3D Camera was employed for hand gesture recognition. The two-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…In the context of pervasive displays research, many touchless gestural interfaces have been proposed and implemented. They have been used in order to interact with 3D virtual objects [7], to access information provision systems [8,19], to create and support playful interactions [26], and in many other applications. The use of touchless gestures, especially when applied to public displays, has many advantages.…”
Section: Gestural Interfaces and The Use Of Avatarsmentioning
confidence: 99%
“…In the context of pervasive displays research, many touchless gestural interfaces have been proposed and implemented. They have been used in order to interact with 3D virtual objects [7], to access information provision systems [8,19], to create and support playful interactions [26], and in many other applications. The use of touchless gestures, especially when applied to public displays, has many advantages.…”
Section: Gestural Interfaces and The Use Of Avatarsmentioning
confidence: 99%
“…Previous work has extensively explored mid-air input as a modality for human-computer interaction and designed its use for contexts, such as cars [13], clean rooms in industrial settings [14], and for retail situations [15], but also for pervasive displays [5,6]. Aslan et al [16] showed that interfaces reacting to the movement of a user's hand before any touch event happens can appear more attractive to the user.…”
Section: Mid-air Interaction and User Experiencementioning
confidence: 99%
“…In order to explore this notion of interacting with an intelligent digital canvas, we developed a drawing application based on reinforcement learning. Since mid-air pointing seems to be an engaging, "natural", and flexible way to draw on pervasive displays (e.g., [5,6]) we decided to integrate it as an alternative interaction technique for users. Before we describe the design of the drawing application in detail and report on a qualitative user study with a heterogeneous group of users we provide the necessary background in reinforcement learning and related work in mid-air interaction in the next section.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of pervasive displays research, many touchless gestural interfaces have been proposed and implemented. They have been used in order to interact with 3D virtual objects [6], to access information provision systems [7,18], to create and support playful interactions [23], and have many other applications. The use of touchless gestures, especially when applied to public displays, has many advantages.…”
Section: Gestural Interfaces and The Use Of Avatarmentioning
confidence: 99%